A conceptual framework for an effective economic valuation of heritage building - Junainah Mohamad; Suriatini Ismail; Rosdi Ab. Rahman (Universiti Malaysia Kelantan, 2015)
The economic valuation of non-market goods specifically heritage building has faced many challenges over the time. Valuation is part of decision making process for the preservation and protection of heritage building. Contingent Valuation Method (CVM) is the most popular method for heritage building valuation. However, over the past two decades this method has received many criticisms due to potential biased estimation. This paper presents a conceptual framework for an effective economic valuation of heritage building based on CVM